Microbe-aided thermophilic composting accelerates manure fermentation - Wang, Likun; Li, Yan; Li, Xiaofang (Frontiers in Microbiology, 2024)
Aerobic composting is a key strategy to the sustainable use of livestock manure, which is however constrained by the slow kinetics. Microbe-aided thermophilic composting provides an attractive solution to this problem. In this study, we identified key thermophilic bacteria capable of accelerating manure composting based on the deciphering of manure bacterial community evolution in a thermophilic system. High-throughput sequencing showed a significant evolution of manure bacterial community structure with the increasing heating temperature. Firmicutes were substantially enriched by the heating, particularly some known thermotolerant bacterial species, such as Novibacillus thermophiles, Bacillus thermolactis, and Ammoniibacillus agariperforans. Correspondingly, through function prediction, we found bacterial taxa with cellulolytic and xylanolytic activities were significantly higher in the thermophilic process relative to the initial stage. Subsequently, a total of 47 bacteria were isolated in situ and their phylogenetic affiliation and degradation capacity were determined. Three isolates were back inoculated to the manure, resulting in shortened composting process from 5 days to 3 days with Germination Index increased up to 134 %, and improved compost quality particularly in wheat growth promoting. Comparing to the mesophilic and thermophilic Bacillus, the genomes of the three isolates manifested some features similar to the thermophiles, including smaller genome size and mutation of specific genes that enhance heat tolerance. This study provide robust evidence that microbe-aided thermophilic composting is capable to accelerate manure composting and improve the quality of compost, which represents a new hope to the sustainable use of manure from the meat industry.